Nutritional assessment as predictor of complications after hematopoietic stem cell transplantation - Marcela Espinoza; Javiera Perelli; Roberto Olmos; Pablo Bertin; Verónica Jara; Pablo Ramírez (Revista Brasileira de Hematologia e Hemoterapia, 2016)
ABSTRACT Introduction: Nutritional support is pivotal in patients submitted to hematopoietic stem cell transplantation. Nutritional status has been associated with time of engraftment and infection rates. In order to evaluate the association between nutritional parameters and clinical outcomes after transplantation a cohort of transplant patients was retrospectively evaluated. Methods: All 50 patients transplanted between 2011 and 2014 were included. The nutritional status before transplantation, ten days after transplantation and before discharge was assessed including anthropometry, body mass index, albumin, prealbumin and total urinary nitrogen. Results: The median follow-up time was 41 months and the median age of patients was 41 years. Thirty-two underwent allogeneic and 18 autologous transplants. Diagnoses included acute leukemias (n = 27), lymphoma (n = 7), multiple myeloma (n = 13), and aplastic anemia (n = 3). Thirty-seven patients developed mucositis (three Grade 1, 15 Grade 2, 18 Grade 3 and one Grade 4), and twenty-two allogeneic, and five autologous transplant patients required total parenteral nutrition. Albumin and total urinary nitrogen were associated with length of hospital stay and platelet and neutrophil engraftment. None of the nutritional parameters evaluated were associated with overall survival. Non-relapse mortality was 14% and overall survival was 79% at 41 months of follow-up. Conclusions: After hematopoietic stem cell transplantation, high catabolism was associated with longer length of hospital stay, the need of total parenteral nutrition and platelet and neutrophil engraftment times. Nutritional parameters were not associated with overall survival.